In the eyes of men: Analysis of men first impression formation on Tinder - Gerson Ralph Manuel Kho (Universitas Bunda Mulia, 2022)
Do not judge the book by its cover. As good as it may sound, it is almost impossible to do so. As inquisitive human nature, we judge people based on what we see on them; the first time we meet them. Even though we did that many times and every time we meet someone new, the research in the field of first impression is little in numbers if we are about to compare within the field of communication science. On top of that, with the development of communication technology, people are seeking someone new as a potential life partner through virtual space. This research employed a qualitative approach to seeking the answer about